PSYCHOMETRIC ANALYSIS OF MATHEMATICS READINESS ASSESSMENT TOOL FOR ELEMENTARY SCHOOL STUDENTS: A RASCH MODEL APPROACH - SHEPTIAN, RIKY; ARTHUR, RIYAN; WARDHANI, RAHAYU (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This study examines the psychometric properties of a Mathematics Readiness Assessment Tool for elementary school students using Rasch analysis through the Winstep program. The analysis involved 214 students responding to 15 items. Results show strong psychometric characteristics with an item reliability of 0.95 and person reliability of 0.69. The instrument demonstrates good construct validity with INFIT and OUTFIT MNSQ values falling within the acceptable range (0.5-1.5). Analysis of unidimensionality showed satisfactory results with raw variance explained by measures at 26.8% and unexplained variance in the first contrast at 7.6%. Local independence assumption was met with residual correlations ranging from -0.22 to 0.20. Item difficulty ranges from -1.33 to 1.56 logits, indicating a good spread of item difficulties. The test information function shows optimal measurement precision for students of average ability levels, though less precise for extremely high or low abilities. Differential Item Functioning (DIF) analysis revealed some items requiring revision, particularly items 13-15. The instrument's Alpha Cronbach value of 0.73 indicates good internal consistency. Overall, the assessment tool demonstrates adequate psychometric properties for measuring mathematics readiness in elementary school students, though some improvements are recommended for optimal measurement across all ability levels.